2019
DOI: 10.1109/access.2019.2954590
|View full text |Cite
|
Sign up to set email alerts
|

CE-HEAT: An Aspect-Level Sentiment Classification Approach With Collaborative Extraction Hierarchical Attention Network

Abstract: Aspect-level sentiment classification is a fine-grained sentiment analysis task. It aims to predict the sentiment of a review in different aspects. Recently many works exploit the hierarchical attention network to capture the aspect-specific sentiment information. However, the prior work only attends to use the aspect terms to capture the aspect-specific sentiment information in the text. It may cause the mismatch of sentiment for the aspect-specific when the aspect words are extracted incorrectly. Since the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…One-unit extracts attribute and use them to capture specific information about the other layer. Experiments show that the proposed approach performed better than recent methods that only use aspect features [ 26 ]. Emotional vocabulary is an important source of thought extraction.…”
Section: Literature Of Opinion Miningmentioning
confidence: 99%
“…One-unit extracts attribute and use them to capture specific information about the other layer. Experiments show that the proposed approach performed better than recent methods that only use aspect features [ 26 ]. Emotional vocabulary is an important source of thought extraction.…”
Section: Literature Of Opinion Miningmentioning
confidence: 99%
“…The upgraded ALBERTC network was utilized to extract global phrase information and local emotion data while representing the initial aspect-level text as a word vector. Additionally, Gao et al (2019) have suggested the CE-HEAT approach to extract the uncommon sentiment terms. It has two hierarchical attention units, the first one collects sentiment characteristics from the sentiment attention layer.…”
Section: Literature Surveymentioning
confidence: 99%
“…Han et al [46] proposed a Multi-Attention Network (MAN) model which adopts several attention networks, the model solve the problem of the RNN-based model can't extract the potential correlation between relatively distant sentiment words and aspect words in complex statements, and the proposed model could achieve consistently superior results on three datasets. Gao et al [47] propose a collaborative extraction hierarchical attention network, this proposed method achieves better performance than the methods which only use aspect features to extract sentiment feature for aspect-level sentiment classification on SemEval competition data set. Yuan et al [48] proposed a sentiment analysis model based on multi-channel convolution and bidirectional GRU networks, and introduced an attention mechanism on the [50] proposed a bidirectional long short-term memory (BiLSTM) network with the multi-head attention mechanism model for sentiment analysis.…”
Section: Related Workmentioning
confidence: 99%